Groundwater evaluation of northern Jazmourian (south Iran) for drinking, agriculture, and associated health risks of nitrate and fluoride contamination. Issue 1 (1st February 2023) - Abbasnejad, Behnam; Abbasnejad, Ahmad; Derakhshani, Reza
Abstract: To investigate groundwater quality in the north of Jazmourian (Roudbar plain), 30 samples were collected and analyzed for evaluating drinking and irrigation status and associated health risks. In addition to major anions and cations, the fluoride and nitrate content of samples were analyzed using standard procedures. Nitrate levels range between 6.6 and 131 mg/L and exceed the WHO permissible limit in more than 23% and 80% of samples for adults and children, respectively. Fluoride amounts ranged from 0.4 to 4.8 mg/L in samples. The F - level exceeded the WHO standard limit in 10% of samples. The EC level increases in fine-grained deltaic deposits toward the south. The concentrations of major ions (HCO3, Cl, SO4, Mg, Na, K) increase southwards, following the flow direction. There are, however, lateral (east-west) differences in water quality due to the influence of such factors as the rate of recharge and the type of bedrock. Wherever the redbeds comprise the bedrock and the recharge rate is weaker, the dissolved salts are higher in amount. The water quality index (IWQ) indicated that 13, 13, and 4 samples are in "good, " "poor, " and "very poor" quality classes, respectively. By using the irrigation water quality index (IWQI), eight samples were at "low restriction, " nine samples at "moderate restriction, " twelve samples at "high restriction, " and one sample at "severe restriction" classes. The acquired findings revealed that the mean oral hazard quotient of nitrate was 1.14, 1.0, and 0.84, and for fluoride, it was 0.82, 0.72, and 0.61 for children, females, and males, respectively. The total hazard index for cumulative NO3 - and F - toxicity exceeded the acceptable level in 76.67%, 66.67%, and 56.67% of samples for children, females, and males, respectively.